The Reliability of Histamine Pharmacodynamic Response Phenotype Classification in Children With Allergic Disease - Kumar, Shaun S.; Liu, Xiaoxi; Sherwin, Catherine M.; Jones, Bridgette L. (Frontiers in Pharmacology, 2020)
We have identified distinct histamine pharmacodynamic response phenotypes in children with allergic disease utilizing Histamine iontophoresis with laser Doppler (HILD). These response phenotypes may be relevant in guiding therapeutic decision making for agents targeting the allergic response pathways. However, the reliability of these response phenotypes has not been assessed. Therefore, we performed HILD in children with allergic rhinitis and/or asthma on two to three separate occasions. HILD response-time data were analyzed in NONMEM using a linked effect PKPD model. Examination of observed versus classified response phenotypes predicted response plots and the sum of residuals. The interclass correlation coefficient (ICC) was used to determine the reliability of phenotype classification. Eighty-two percent of children exhibited a reliable histamine response phenotype (Intraclass correlation coefficient 0.77 (95% CI 0.44 – 0.93). These preliminary results suggest moderate reliability of HILD response phenotype in children. Further exploration is needed to determine contributions to phenotype variability.